استراتيجيات تهديد الوجه وصيانته في خبر الأصمعي مع ولد حاتم وامرأة من ولد ابن هرمة في ضوء نظرية التأدب - آل جهجاه، الجوهرة بنت بخيت (جامعة أم القرى, 2020)
This research analyzes the selected text for the pragmatic study in the light of the concept of Face, which its model developed by Brown and Levinson in 1978 in the context of the theoretical principles of politeness. It is taken from two angles; one is concerned with the speaker and the strategies he has chosen to select the positive and negative faces targeted by his threats and then the strategies that he has diversified his successive threats on. The research then moves on to analyze the strategies of the addressee that he creates in order to repel or mitigate those threats or their damage to the speaker's face. Keeping the addressees in line with the speaker has emerged in his strategies by threatening him with some similar strategies or mitigating it in their attempts to preserve their faces, which made the interactive speech maneuver a conflict maneuver in which the speaker lost it to the outspoken man in his defense of the two aspects of his face and returned the attack on both aspects of the speaker's face, while addressing the female, who has successive positive politeness strategies through, he exchanged her with strategies to mitigate threats and remedy the risks to accomplish his quest to make her a victim for irony, he had passed through the strategy of negative politeness (praising).
يحلل هذا البحث نص الخبر المختار للدراسة التداولية في ضوء مبدأ الوجه الذي وضع نموذجه (براون) و(ليفنسون) عام 1978م؛ في سياق المبادئ التنظيرية للتأدب؛ وذلك من زاويتين تعنيان بالمتكلم والاستراتيجيات التي اتخذها في انتقاء الوجوه الجالبة والدافعة التي استهدفها بتهديداته، ومن بعدها الاستراتيجيات التي نوع تهديداته المتوالية عليها، ثم انتقل البحث إلى تحليل استراتيجيات المخاطب التي يبنيها لصد تلك التهديدات أو تلطيفها وتخفيف إضرارها بوجه المتكلم. وقد برزت مجاراة المخاطبين للمتكلم في استراتيجياته من خلال تهديده بما يماثلها أو التخفيف من حدتها في محاولاتهما صيانة وجهيهما؛ مما جعل الموقف التفاعلي التخاطبي مناورة صراع؛ خسر المتكلم فيها أمام المخاطب الصريح في دفاعه عن جانبي وجهه، وإعادة الهجوم إلى جانبي وجه المتكلم؛ في حين بادل المخاطبة التي تتابعت لديها استراتيجيات التأدب الجالب من خلال أفعال الاعتذار غير المباشرة - بادلها باستراتيجيات تلطيف التهديدات وإصلاح مخاطرها؛ لينجز سعيه إلـى جعلها ضحية لمقصد السخرية الذي مرره من خلال استراتيجية التأدب الدافع (الثناء).
Keywords: الأدب العربي -- النقد الأدبي -- الأصمعى، عبدالملك بن قريب بن عبدالملك، ت. 216 هـ